2021
DOI: 10.1111/os.13151
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Outcomes between Robot‐Assisted Minimally Invasive Transforaminal Lumbar Interbody Fusion and Oblique Lumbar Interbody Fusion in Single‐Level Lumbar Spondylolisthesis

Abstract: Objective: To compare the safety and effectiveness of robot-assisted minimally invasive transforaminal lumbar interbody fusion (Mis-TLIF) and oblique lumbar interbody fusion (OLIF) for the treatment of single-level lumbar degenerative spondylolisthesis (LDS).Methods: This is a retrospective study. Between April 2018 and April 2020, a total of 61 patients with single-level lumbar degenerative spondylolisthesis and treated with robot-assisted OLIF (28 cases, 16 females, 12 males, mean age 50.4 years) or robot-as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
41
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(44 citation statements)
references
References 29 publications
0
41
0
Order By: Relevance
“…The RCT scored 8 points ( 8 ). The NOS score results for the 12 cohort studies were as follows: 3 articles scored 5 points ( 9 , 10 , 11 ), 5 articles scored 6 points ( 12 , 13 , 14 , 15 , 16 ), 3 articles scored 7 points ( 17 , 18 , 19 ), and 1 article scored 8 points ( 20 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The RCT scored 8 points ( 8 ). The NOS score results for the 12 cohort studies were as follows: 3 articles scored 5 points ( 9 , 10 , 11 ), 5 articles scored 6 points ( 12 , 13 , 14 , 15 , 16 ), 3 articles scored 7 points ( 17 , 18 , 19 ), and 1 article scored 8 points ( 20 ).…”
Section: Resultsmentioning
confidence: 99%
“…A total of 7 studies ( 9 , 10 , 13 , 16 , 17 , 19 , 20 ) reported the postoperative IH, including 546 patients, 278 patients in the OLIF group and 268 patients in the TLIF group. The heterogeneity between the two groups was high ( P < 0.1, I 2 = 75%), and the results showed ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations